Application and Evaluation of Management by Objective Model (Mbo) in Garment Manufacturing Industries: An Empirical Study in Respect of Ten Companies at Export Processing Zone - Stanley, P. D. G. (A thesis submitted for the Master of the Business Administration Degree, 1992)
The Garment manufacturing industry plays a significant role in Sri Lanka’s economy. The textile and garment manufacturing sector contributed 31% out of total exports during the year 1990. The garment manufacturing industry started its operations under G.C.E.C. Act No. 04 of 1978. Most of these garment factories at Katunayake are owned by 100% foreign companies or foreign collaborated companies with local partners. …